Diversity of Saltpan Marine Cyanobacteria from Cape Comorin Coast of Tamilnadu - Rajarathinam2, A. Jeevarathinam1, D. Abirami1 and M. Bhoothapandi1, R. Sugumar1, G. Ramanathan1*, K. (Journal of Phytology, 2011)
Cyanobacteria are photosynthetic prokaryotes, which are found in a wide variety of habitats, namely, fresh water, marine, moist soil, saline and sodic soil as well as in thermophilic and psychrophilic conditions. In many environments, cyanobacteria are the primary producers at the base of the food web of the ecosystem such as marine water, hypersaline, brackish waters, soda lakes, freshwater, paddy fields, soils, deserts, cave walls, hot springs, polar regions and other extreme environments. Excess salt concentrations in sea water are said to be hypersaline environments. Salt pans are one of the hypersaline extreme environment exhibit wide range of environmental stress through salinity changes. The biodiversity of marine cyanobacteria were investigated in three salt pan regions such as Kovalam, Puthalam and Rajakamangalam in Kanyakumari district, Tamil Nadu, India. The cyanobacterial mats were cultivated in three different cultivation media such as ASNIII, MNIII and BG11 marine broth. Morphological characterization was done. Among the saltpan studied for cyanobacterial diversity Kovalam site showed about twelve genera of cyanobacteria such as Oscillatoria, Lyngbya, Microcystis, Spirullina, Chroococcus and Calothrix were dominant with 18 cyanobacterial species under five families were reported when compared with other two saltpan regions studied.